TOWARDS AN INFRASTRUCTURE-BASED SOCIOLOGY OF DIGITAL SOVEREIGNTY PRACTICES: THE 'PILOT CASE' OF RUSSIA - Musiani, Francesca (AoIR Selected Papers of Internet Research, 2021)
"Digital sovereignty" is the idea that states should “reaffirm” their authority over the Internet and protect their citizens, institutions, and businesses from the multiple challenges to their nation’s self-determination in the digital sphere. According to this principle, sovereignty depends on more than supranational alliances or international legal instruments, military might or trade: it depends on locally-owned, controlled and operated innovation ecosystems, able to increase states’ technical and economic independence and autonomy. Presently, digital sovereignty is understood primarily as a legal concept and a set of political discourses. As a consequence, it is predominantly analysed by political science, international relations and international law. However, the study of digital sovereignty as a set of infrastructures and socio-material practices has been largely neglected. In this proposal, I argue that the concept of (digital) sovereignty should also be studied via the infrastructure-embedded “situated practices” of various political and economic projects which aim to establish autonomous digital infrastructures in a hyperconnected world. Although this contribution is also a call for a wider and comparative research programme, I will focus here on the “pilot case” of Russia, which is the subject of an ongoing research project. Ultimately, the analysis of infrastructure-embedded digital sovereignty practices in Russia shows how the Russian discourse on Internet sovereignty as a centralized and top-down apparatus paradoxically open up technical and legal opportunities for mundane resistances and the existence of “parallel” Runets, where particular instantiations of informational freedom are still possible.